Struktur Komunitas Fitoplankton di Sungai Teluk Nibung pada Kawasan Mangrove Kecamatan Batu Ampar Kabupaten Kubu Raya - Qairunisa, Maya Rahmadanty; Daningsih, Entin; Candramila, Wolly (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Teluk Nibung River in Batu Ampar District, Kubu Raya Regency is a transportation route for Mangrove Production Forests and a traditional fishing area for local communities. The community structure of phytoplankton in the Teluk Nibung River has never been reported. As the main producer in the waters food chain, the structure community of phytoplankton indicates the quality of the fertility of the waters. The community structure of phytoplankton can be identified by measuring the index of abundance, diversity, evenness and dominance. The survey method was used at three stations in dry and rainy seasons. Sample collection is using net plankton (30Â Âµm) and preserved in 4% formalin. The physico-chemical factors measured included temperature, pH, brightness, current velocity, salinity, dissolved oxygen and CO2, phosphate and nitrate. Once identified, phytoplankton calculations are performed to obtain abundance, diversity, evenness, and dominance values. The species number of phytoplankton found was 56 classified into 6 classes, namely Bacillariophyceae (34 species), Dinophyceae (12 species), Chlorophyceae (4 species), Cyanophyceae (3 species), Xantophyceae (1 species), and Euglenophyceae (2 species). The highest abundance of phytoplankton was in the Bacillariophyceae class with a range of 583 Ind./L at Station 2 in the rainy season to 3.922 Ind./L at Station 3 in the dry season. The diversity index at the three stations and both seasons is in the moderate category with a range of 2.31-2.46. The evenness index at the three stations and both seasons is in the high category with a range of 0.67-0.73. Low dominance level was found at the three stations and both seasons with values ranging from 0.14 to 0.19. Overall, the community structure of the phytoplankton in the Teluk Nibung River is in relatively good condition and can support the life of the aquatic biota in it.